Body Language Detecting Deception: Fatima Fatima - Fatima, Fatima Fatima (International Journal for Electronic Crime Investigation, 2020)
AbstractThe objective of this review paper is to discuss the understanding of body language deception. Thisstudy explains a detail interpretation of body language also known as nonverbal cues including facialexpressions called micro-expressions and other bodily moves of speakers/suspects during interviewsand investigation process. It will emphasize on importance of reading body language in criminalinvestigation for lie detection and proper training of investigators/interviewers for an effectiveinterrogation. It explains proper documentation of nonverbal cues and recording them for furtherassistance in multiple interviews in future as these cues remain for a short time. It will enlighten theeffects of gender, social and economic status on body language and their resulting cues. A properknowledge and training of reading nonverbal behaviors can increase forensic application of bodylanguage in criminal justice system for the identification of the right guilty party.